An Unusual Narrow QRS Complex Tachycardia: What Is the Mechanism?. Issue 1 (9th July 2014) - Carbone, Vincenzo; Marafioti, Vincenzo; Oreto, Giuseppe
<x xml:space="preserve">Abstract</x> The electrocardiogram of a 72‐year‐old woman showed episodes of nonsustained narrow QRS complex tachycardia. Tracing analysis suggested that the arrhythmia was due to interpolated atrial extrasystoles occurring in bigeminal rhythm. Interpolation of atrial extrasystoles is a rare phenomenon. In this condition, a premature atrial beat is "sandwiched" between 2 normal sinus beats, and sinus PP interval containing the extrasystole is often longer than unaffected sinus cycles. Alternative mechanisms for the arrhythmia are discussed, such as: (1) sinus node reentry; (2) 1:2 response to atrial ectopy over the fast and the slow atrioventricular nodal pathways; and (3) couplets of atrial extrasystoles.